Leidersblad (Brussel: NVSM)
"Bibliotheek E. AnseeleHoofdredactie, beheer en administratie: Kernstraat 21, BrusselRedactie: A. Jauniaux, V. Mulkers, Tysebaert, Victor GraulsDrukker/Drukkerij: C. Robberecht-Merckx, Oude Vest 23, Dendermonde (feb 1935)"